Herbal Plant Farming Development Strategy - Eliyatiningsih Eliyatiningsih; Iqbal Erdiansyah; Vega Kartika Sari; Dwi Nurahmanto (Program Studi Agribisnis, Fakultas Pertanian, Universitas Udayana Jalan PB.Sudirman Denpasar, Bali, Indonesia. Telp: (0361) 223544 Email: soca@unud.ac.id, 2023)
The demand for herbal plants has increased significantlyin the last few years, especially during the covid 19pandemic. People believe that herbal products have savorsto maintain body immunity. The purpose of this study wasto analyze internal factors (strengths and weaknesses) andexternal factors (opportunities and threats), formulatepolicies, and identify priority strategies that can be appliedby farmers in developing herbal farming. This researchhad conducted in Pace Village, Silo District, JemberRegency, from August to November 2021. The analysisused internal and external factors analysis, SWOT matrix,and QSPM analysis to determine priority strategies. Theinternal and external factor analysis showed that herbalplant farming was in Region V with defend and maintainposition. Based on the SWOT matrix, eight strategies hadearned to develop a herbal business. Based on the QSPManalysis, the key strategy was to increase farmers'knowledge regarding the prospects and marketing ofherbal plants, with a total value of 8.365